2003
DOI: 10.1002/ijc.11175
|View full text |Cite
|
Sign up to set email alerts
|

Distinct methylation profiles of glioma subtypes

Abstract: Gliomas are tumors of the central nervous system with a wide spectrum of different tumor types. They range from pilocytic astrocytoma, with a generally good prognosis, to the extremely aggressive malignant glioblastoma. In addition to these 2 types of contrasting neoplasms, several other subtypes can be distinguished, each characterized by specific phenotypic, as well as genotypic features. Recently, the epigenotype, as evident from differentially methylated DNA loci, has been proposed to be useful as a furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 18 publications
4
51
0
1
Order By: Relevance
“…In accordance with previous studies, high methylation rates were found for CDKN2A 17, CDKN2B 18, and RASSF1A 8, suggesting that aberrant methylation of these genes may indicate early change in tumorigenesis of oligodendroglial tumors, regardless of cell type. Both CDKN2A and CDKN2B, tumor suppressor genes encoding p16 (INK4a) and p15 (INK4b), respectively, which are localized to 9p21 and act via the Rb and p53 pathways, have been found to be aberrant to some degree in gliomas 21, 22.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous studies, high methylation rates were found for CDKN2A 17, CDKN2B 18, and RASSF1A 8, suggesting that aberrant methylation of these genes may indicate early change in tumorigenesis of oligodendroglial tumors, regardless of cell type. Both CDKN2A and CDKN2B, tumor suppressor genes encoding p16 (INK4a) and p15 (INK4b), respectively, which are localized to 9p21 and act via the Rb and p53 pathways, have been found to be aberrant to some degree in gliomas 21, 22.…”
Section: Discussionsupporting
confidence: 91%
“…The ME002 Kit was chosen because it included the analysis of genes playing important roles in cell‐cycle control, transcription regulation, and cell differentiation and proliferation. This kit has been widely used to investigate the methylation status in studies of breast cancer, prostate cancer, and neuroblastoma 14, 15, 16.The results are concordant with previous reports revealing alterations in the methylation profiles of several genes in patients with oligodendroglial tumors, including TIMP3 17, CDKN2A 17, CDKN2B 18, CDKN1B, PTEN 8, RASSF1A 8, DAPK1 17, ESR1 18, TP73 17, and GSTP1 17.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This gene encodes the inducible isozyme, and is misregulated in many cancers (Rizzo, 2011). Hypermethylated PTGS2 has been reported for gliomas, gastric carcinomas, prostate cancer, and breast cancer, among others (Uhlmann et al, 2003;Yu et al, 2003;Yegnasubramanian et al, 2004;Chow et al, 2005). Ellinger and colleagues detected PTGS2 CpG island hypermethylation in the cell-free circulating serum DNA of TGCT patients at a frequency of ~45%; no differences were observed between patients with seminomas and those with non-seminomas (Ellinger et al, 2009).…”
Section: Ptgs2 (Oxidation-reduction)mentioning
confidence: 99%
“…Over recent years aberrant DNA methylation was shown to be a common molecular lesion in human tumors as well, which had also impact on patient prognosis and treatment response. Epigenetic silencing of p16 and p15 was shown in a variety of human neoplasms, in glioma patients hypermethylation is reported in about 30% of the cases (18)(19)(20)(21). Whereas in other tumors inactivation of both tumor suppressor genes was associated with prognosis and response to chemotherapy, a prognostic and predictive role in gliomas is not shown (9,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%